Food for All in a Sustainable World : The IIASA Food and Agriculture Program. - Parikh, Kirit; Rabár, Ferenc (Laxenburg AU: Internationa Institute for Applied System Analysis, 1981)
Seminario del Programa Alimentaciòn y Agricultura en la Conferencia de 1981 y las actividades del Instituto Internacional de los Sistemas de Analisis Aplicados (ASA)
Summarizing presentations at the IIASA Food and Agriculture Program Status Report Conference, February 1981.
Keywords: SEMINARIOS; CONFERENCIAS; AGRICOLTURA; INSTITUTO INTERNACIONAL DE LOS SISTEMAS DE ANALISIS APLICADOS